2018
DOI: 10.1016/j.ctcp.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Acute responses of cytokines and adipokines to aerobic exercise in relapsing vs. remitting women with multiple sclerosis

Abstract: After relapse, exercise does not induce inflammatory cytokine response and temporarily improves both cytokine and adipokine balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 33 publications
(70 reference statements)
1
27
0
Order By: Relevance
“…This inflammatory hypothesis is supported by findings from clinical studies and animal experiments showing that anti-inflammatory agents attenuated neuronal dysfunction in AD [27,28]. Physical exercise confers broad anti-inflammatory effects in many neurodegenerative diseases, probably by affecting the secretion of inflammatory cytokines/adipokines via the muscle-adipose crosstalk [29,30]. It has been shown that exercise can improve the immune status of the brain, either by inhibiting the production of pro-inflammatory factors such as IL-1β [31], or by promoting the synthesis of anti-inflammatory factors such as IL-10 [32].…”
Section: Discussionmentioning
confidence: 83%
“…This inflammatory hypothesis is supported by findings from clinical studies and animal experiments showing that anti-inflammatory agents attenuated neuronal dysfunction in AD [27,28]. Physical exercise confers broad anti-inflammatory effects in many neurodegenerative diseases, probably by affecting the secretion of inflammatory cytokines/adipokines via the muscle-adipose crosstalk [29,30]. It has been shown that exercise can improve the immune status of the brain, either by inhibiting the production of pro-inflammatory factors such as IL-1β [31], or by promoting the synthesis of anti-inflammatory factors such as IL-10 [32].…”
Section: Discussionmentioning
confidence: 83%
“…Weight gain is associated with releasing leptin from adipose tissue which stimulates proinflammatory cytokines produced from T helper 1 cells such as TNFα (Majdinasab et al, 2018;Mokhtarzade et al, 2017). In addition, there are more macrophages, T cells, and inflammatory molecules connected with more subcutaneous adipose tissues (Esser et al, 2014).…”
Section: Exercise-related Neurotrophic Factors Modulationmentioning
confidence: 99%
“…
Exercise-induced changes in neurotrophic factors and markers of blood-brain barrier permeability are moderated by weight status in multiple sclerosis Ranjbar, R. (2018). Exercise-induced changes in neurotrophic factors and markers of blood-brain barrier permeability are moderated by weight status in multiple sclerosis.
…”
mentioning
confidence: 95%
“…Multiple sclerosis (MS) is a common neurological disease of the central nervous system (CNS) that occurs when lymphocytes cross the blood–brain barrier (BBB) and initiate axonal demyelinating processes . MS is further characterized by the presence of plaques in the brain that are detectable through magnetic resonance imaging (MRI), disturbances in neurotrophic factors, BBB dysfunction and accelerated whole‐brain atrophy .…”
Section: Introductionmentioning
confidence: 99%